The adventures of Tom Sawyer - Twain, Mark, 1835-1910. (Mineola, N.Y. : Dover Publications, 1998)
An unabridged republication of the 1876 novel about the adventures of a young boy in nineteenth-century rural America.
Adult
Keywords: Boys -- Missouri -- Fiction; Sawyer, Tom (Fictitious character) -- Fiction; Adventure fiction; Boys -- Fiction; Sawyer, Tom (Fictional character) -- Fiction; Missouri -- Fiction; Adventure stories